Incidence of meningitis in term neonates with sepsis and antibiotic sensitivity pattern: an observational study - V. V., Lakshmi Aparna Devi; Soren, Chapay; Umadevi, M.; Pradeep, R. (International Journal of Contemporary Pediatrics, 2019)
Background: To find out the incidence of meningitis in neonatal sepsis and antibiotic sensitivity pattern in term neonates. Methods: This prospective observational cohort study was done in a tertiary care hospital located in rural South India for a period of 2 years. Blood culture and lumbar puncture were performed for all term babies with clinically suspected sepsis. Growth, if detected was followed by antibiotic sensitivity testing. Results: Of a total of 50 neonates investigated with blood culture, 32(64%) were found to be culture positive for neonatal septicemia, 16 were diagnosed to have meningitis. Meningitis was present in 4(25%) early onset sepsis cases and in 12(75%) late onset sepsis cases (p-value: 0.008). Blood culture showed growth in all of the 16 cases of meningitis, but Cerebro Spinal Fluid (CSF) culture was positive in 5 cases. The most common presenting features are lethargy, seizures, decreased acceptance of feeds, instability of temperature regulation, vomiting, respiratory distress, and apnea. The most common organism in blood culture was Coagulase Negative Staphylococcus (CONS) (20%) followed by Klebsiella spp. (16%). CONS was most sensitive to Linezolid (100%), Vancomycin (90%). Of the 8 cases of Klebsiella, 62.5% cases were sensitive to Colistin and Tigecycline, 50% to Cotrimoxazole. CSF culture was positive in 5(31.25%) cases. CONS and Enterococci spp. were the most common organisms isolated in CSF. Conclusions: Clinical manifestations of meningitis overlap with those of sepsis and are nonspecific. Significant number of neonates with sepsis have meningitis. Hence, it is necessary to rule out meningitis in neonates presented with clinical features of sepsis. CONS was the most common agent isolated in both blood and CSF culture. Routine bacterial surveillance and study of their resistance patterns must be an essential component of neonatal care which helps in implementation of a rational empirical treatment strategy.